LIFE STYLE OF RENTED LAND OWNERS IN UBUD SUBDISTRICT - Putra Pemayun, A.A. Gde (E-Journal of Cultural Studies; Volume 7, Number 4, November 2014, 2015)
This present study was intended to analyze the Life Style of the Rented Land Owners at Ubud Subdistrict. The problems of the study are formulated as follows: (1) what is the characteristic of the rented land owners at Ubud Subdistrict like? (2) How has the process of life style of the rented land owners at Ubud Subdistrict  taken place? And (3) what is the implication of the life style of the rented land owners on their lives? Qualitative method was employed in the study. The data were processed using observation, interview and documentary techniques. The workability of the law regulating the demand for land at Ubud Subdistrict motivated the land owners to rent out their land to investors. Apart from that, the internal dimension, which is made up of the economical capital, was the most important element as it could activate small, medium and big enterprises. Another aspect was image which was reflected through perception, cognition, motivation, and attitude of individuals as consumers. As an illustration, they built luxurious houses and showed off luxurious cars to show the image that they were new wealthy people. On the other hand, there was external dimension, namely, the highly rapid development of tourism, which could positively and negatively contribute to the life style of the people living at Ubud Subdistrict. Such an implication could not be avoided. The other aspect was consumerism; the consumers were around the symbol and sign. Mass media were the miracles of the object liturgy; pleasure was defined as the realization of freedom, and the human body was the main object of consumers. The last aspect was the government’s policy which determined that Ubud Subdistrict was a tourist destination. As a result, the local people had the opportunity to rent out their land which was used to expand the industry of tourism and to activate the other economic enterprises.
Keywords: life style, hedonist, consumerism, image.